ANALYSIS OF COLLABORATIVE GOVERNANCE FOR THE DEVELOPMENT OF BETAWI VILLAGE TOURISM IN SETU BABAKAN, SOUTH JAKARTA - fajri, rabbiul (Family Welfare Education, 2024)
This research aims to know the processes and factors that influence Collaborative Governance in managing the Setu Babakan Betawi Cultural Village tourist village, South Jakarta. The research used a qualitative descriptive method of the Collaborative Governance theory approach according to Ansell and Gash (2007) as an analytical study in this research. The data collection techniques are through interviews, documentation, and literature study. The results of the research show that the management of the Setu Babakan Betawi Cultural Village has been running effectively, judging from the initial conditions, institutional design, facilitative leadership, and collaboration processes which have produced a collaboration model in the Setu Babakan Betawi Cultural Village. This is due to the influence of resource factors, institutional forms, government programs, and private sector participation. Some challenges must be addressed in maximizing the management of the Setu Babakan village and the limitations of the UPKPB's institutional functions as a regional organizational work unit which is under the authority of the Culture Service. This limits several functions and authorities to support development in the Setu Babakan Betawi cultural village.